2014
DOI: 10.1016/j.jtemb.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and cytotoxic effect of biologically synthesized selenium nanoparticles in comparison to selenium dioxide

Abstract: The present study was designed to evaluate antioxidant and cytotoxic effect of selenium nanoparticles (Se NPs) biosynthesized by a newly isolated marine bacterial strain Bacillus sp. MSh-1. An organic-aqueous partitioning system was applied for purification of the biogenic Se NPs and the purified Se NPs were then investigated for antioxidant activity using DPPH scavenging activity and reducing power assay. Cytotoxic effect of the biogenic Se NPs and selenium dioxide (SeO2) on MCF-7 cell line was assesed by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(142 citation statements)
references
References 25 publications
5
135
1
1
Order By: Relevance
“…These results are compared with earlier study carried out on biosynthesis of selenium nanoparticles with marine bacterial strain Bacillus sp. MSh-1, in which nanoparticles in size range of about 80-220 nm were obtained (Forootanfar et al 2014), while the probiotic lactic acid bacteria such as Lactobacillus and Bifidobacter produced selenium nanoparticles in the size ranges of 100-200 and 400-500 nm, respectively (Eszenyi et al 2011). From the data, it is evident that the strain B. cereus is able to produce selenium nanoparticles with smaller average nanoparticle size and narrow particle size distribution.…”
Section: Morphology and Size Of Selenium Nanoparticlesmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are compared with earlier study carried out on biosynthesis of selenium nanoparticles with marine bacterial strain Bacillus sp. MSh-1, in which nanoparticles in size range of about 80-220 nm were obtained (Forootanfar et al 2014), while the probiotic lactic acid bacteria such as Lactobacillus and Bifidobacter produced selenium nanoparticles in the size ranges of 100-200 and 400-500 nm, respectively (Eszenyi et al 2011). From the data, it is evident that the strain B. cereus is able to produce selenium nanoparticles with smaller average nanoparticle size and narrow particle size distribution.…”
Section: Morphology and Size Of Selenium Nanoparticlesmentioning
confidence: 97%
“…A wide variety of properties shown by selenium nanoparticles are free radical scavenging (Huang et al 2003), antioxidant (Forootanfar et al 2014;Kong et al 2014;Mittal et al 2014;Ramya et al 2015;Rezvanfar et al 2013;Torres et al 2012;, chemoprotection against chemotherapy-induced reproductive toxicity (Rezvanfar et al 2013) and UV-induced DNA damage (Prasad et al 2013), immunomodulatory, anti-inflammatory (Wang et al 2014), nanomedicinal , chemotherapeutic and chemoprevention against human melanoma and hepatoma cancers Estevez et al 2014;Peng et al 2007), biofortification (Durán et al 2015), and antitumor and anticancer (Jia et al 2015;Kumar et al 2015;Mittal et al 2014;Ren et al 2013) activities. Other applications include antibacterial, antibiofilm (Bartůněk et al 2015;Hariharan et al 2012;Huang et al 2016;Mittal et al 2014;Ramya et al 2015;Shakibaie et al 2015;Tran and Webster 2011;Wang and Webster 2013), antifungal, antiprotozoan, antitapeworm (Bartůněk et al 2015), antiviral, wound healing (Ramya et al 2015), and cytotoxic (Forootanfar et al 2014;Ramya et al 2015) activities. Other non-biological activities such as zinc adsorption (Jain et al 2015), mercury sequestration (Fellowes et al 2011;Jiang et al 2012), biosensing of H 2 O 2 (Wang et al 2010), solar cell (Panahi-Kalamuei et al 2014), and photocatalysis …”
Section: Introductionmentioning
confidence: 99%
“…1,2 As the selenium nanoparticles (SeNPs) possess antimicrobial and anticancer properties, they can be used as nanomedicines. 3,4 Also, they exhibit less toxicity as compared to their inorganic and organic counterparts. 5 Thus, their methods of synthesis need to be studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, 5-200 nm of SeNPs showed high bioactivity and directly scavenged free radicals in vitro [23,24]. …”
Section: Biosynthesis Of Senps With Bacillus Licheniformismentioning
confidence: 87%